Cardiotrophin-1 is associated with increased risk of arterial stiffness. (February 2015) - Hung, Hao-Chang; Lu, Feng-Hwa; Ou, Horng-Yih; Wu, Hung-Tsung; Wu, Jin-Shang; Yang, Yi-Ching; Chang, Chih-Jen
Aim: Cardiotrophin-1 null mice presented decreased arterial stiffness. The aim of this study is to investigate the relationship between cardiotrophin-1 and arterial stiffness, assessed by brachial-ankle pulse-wave velocity (baPWV).Methods: We enrolled 300 subjects, 200 with baPWV >1400 and 100 with baPWV ≤1400 cm/s.Results: Cardiotrophin-1 levels were significantly higher in subjects with baPWV >1400 than those with baPWV ≤1400 cm/s. The multivariate logistic regression analysis showed that age, prehypertension, hypertension and cardiotrophin-1 were independently associated with baPWV >1400 cm/s after adjusting for gender, obesity, diabetes, homeostasis model assessment-insulin resistance, total cholesterol, high-density lipoprotein cholesterol, triglyceride, high-sensitivity C-reactive protein, creatinine, smoking and habitual exercise.Conclusion: Cardiotrophin-1 is positively related to baPWV independent of traditional cardiometabolic risk factors for arterial stiffness.